MANAJEMEN KINERJA PEMBELAJARAN GURU SMA NEGERI 1 PASUI KABUPATEN ENREKANG - Marham, Marham (Eklektika: Jurnal Pemikiran dan Penelitian Administrasi Pendidikan, 2017)
This study aims to determine the management of learning performance, supporting factors and inhibitors of teacher learning performance at SMA Negeri 1 Pasui, Enrekang Regency. This research is a research with a qualitative approach. The focus in this study is teacher learning management, which includes planning, implementing and evaluating as well as supporting factors and obstacles to teacher learning performance. Collection techniques are interviews, documentation and observation. The results showed (1) the performance of teachers at SMA Negeri 1 Pasui was quite good, although there were some parts that were still lacking, such as the facilities owned by the school were not complete, but the teachers at the school had compiled syllabi and RPP, and mastered the learning material, and were able manage the class well. (2) Factors that support the performance of teachers in schools are the high sense of responsibility of teachers in carrying out their duties in school (3) Factors that inhibit the learning performance of teachers in schools, namely the facilities owned by the school are not complete, the laboratories are still lacking, and the library still has few references and lack of technology mastery.